Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus - Rivera-Quiroz, F. Andrés; Álvarez-Padilla, Fernando (Zootaxa, 2019)
The genus Wulfila O. Pickard-Cambridge 1895 belongs to the family Anyphaenidae Bertkau, 1878, commonly called ghost spiders. Wulfila is endemic to the Americas and currently has 43 valid species; here we describe five new: Wulfila conchamonile spec. nov., W. xilitlensis spec. nov., W. luisi spec. nov., W. unguis spec. nov. and W. phantasma spec. nov. Specimens were collected in Mexico as part of three biological inventories developed in Xilitla, San Luis Potosí, and Atotonilco and Xamaticpac, Veracruz, between 2011 and 2014. In addition, we provide an overview of Wulfila taxonomic literature with a discussion on the genus taxonomy, diagnostic characters, species placement, and novel genital characters.